Breathlessness in hospitalised adult patients. Issue 938 (5th January 2004) - Rao, A B; Gray, D
Abstract : Dyspnoea is defined as a sensation of difficult breathing. It is common in hospitalised patients and is often a harbinger of serious and potentially fatal pathology. The pathophysiology of dyspnoea involves complex interactions between peripheral and central receptors and cognition. Given the myriad causes of dyspnoea, a systematic approach to diagnosis is important. A good history and systemic examination are necessary as it is important to quickly identify the cause and treat it promptly. Investigations are numerous but chest radiography and electrocardiography are among the commonest and most useful. It is important to understand the mechanisms underlying dyspnoea to treat breathless patients successfully.